(untitled) (American Journal of Islam and Society, 2014)
One does not need to repeat the oft-stated observation that editing and translating the epistles of the Brethren of Purity (Ikhwan al-Safa’) will greatly enhance our understanding of the pre-Avicennan period’s intellectual history of the philosophical sciences. Carmela Baffioni, senior research fellow at the Institute of Ismaili Studies, which sponsors this project, is a leading specialist on the Brethren, having spent an illustrious career at Naples – twenty-five items in the bibliography constitute her major contributions, alongside the editions and translations she has contributed to this series. She has already edited and translated the epistles on logic in an earlier volume of this series – those epistles come immediately before the seven that are published here (out of the seventeen epistles that comprise the second section on the natural sciences) and are the culmination of the first section on the mathematical sciences. The volume immediately after on epistle 22 on animals has been published many times and is arguably one of the most famous of the Epistles: The Case of the Animals versus Man before the King of the Jinns (published in this series in the translation of Lenn Goodman and Richard MacGregor). With this highly useful and impressive volume, she has made a major contribution. This large volume (around 1,000 pages of English and Arabic) comprises a foreword by Nader el-Bizri (the project’s general editor); an ...